A multivalent mRNA vaccine elicits robust immune responses and confers protection in a murine model of monkeypox virus infection - Yansheng Li; Lin Cheng; Lixu Jiang; Zhuohuan Li; Jing Rao; Tong Wu; Fangyan Zhang; Baocai Xie; Yu He; Lianrong Wang; Zheng Zhang; Shi Chen (Nature Communications)
Abstract Monkeypox virus (MPXV) has re-emerged globally since May 2022, posing a significant public health threat. To address this, we develop two multivalent mRNA vaccine candidates—AAL, encoding three MPXV antigens, and AALI, which combines AAL with an immune-enhancing IFN-α protein. Both vaccines are delivered via mannose-modified lipid nanoparticles to target dendritic cells. Here we show that these vaccines elicit strong antibody responses against vaccinia virus and multiple MPXV clades, induce robust memory B-cell and T-cell responses, and promote dendritic cell maturation. In mouse challenge models, both vaccines provide protection against clade IIb MPXV and vaccinia virus, significantly reducing viral loads and preventing lung damage. Immune profiling reveals enhanced B- and T-cell receptor diversity and distinct CDR3 motifs post-vaccination. These findings demonstrate the potential of using mRNA-based multivalent vaccines as an effective strategy for preventing mpox and related Orthopoxvirus infections.